Inflammasome NLRP3 activation induced by Convulxin, a C-type lectin-like isolated from Crotalus durissus terrificus snake venom - Rego, Cristina M. A.; Francisco, Aleff F. [UNESP]; Boeno, Charles N.; Paloschi, Mauro V.; Lopes, Jéssica A.; Silva, Milena D. S.; Santana, Hallison M.; Serrath, Suzanne N.; Rodrigues, Jaína E.; Lemos, Caleb T. L.; Dutra, Ricardo S. S.; da Cruz, Jorddy N.; et al. (Springer Nature, 2022)
Convulxin (CVX), a C-type lectin-like protein isolated from the venom of the snake species, Crotalus durissus terrificus, stimulates platelet aggregation by acting as a collagen receptor agonist for glycoprotein VI found in the platelets. The effect of CVX on platelets has been studied, but its effect on human peripheral blood mononuclear cells (PBMCs) remains unclear. Given the significance of PBMCs in inflammation, this study explored the effect of CVX on PBMCs, specifically regarding NLRP3 inflammasome activation by assessing cell viability, ability to induce cell proliferation, reactive oxygen species (ROS) and nitric oxide production, interleukin (IL)-2 and IL-10 secretion, NLRP3 complex activation, and the role of C-type lectin-like receptors (CTLRs) in these. CVX was not toxic to PBMCs at the investigated concentrations and did not increase PBMC growth or IL-2 release; however, CVX induced IL-10 release and ROS generation via monocyte activation. It also activated the NLRP3 complex, resulting in IL-1β induction. Furthermore, the interaction between CVX and Dectin-2, a CTLR, induced IL-10 production. CVX interaction with CTLR has been demonstrated by laminarin therapy. Because of the involvement of residues near the Dectin-2 carbohydrate-recognition site, the generation of ROS resulted in inflammasome activation and IL-1β secretion. Overall, this work helps elucidate the function of CVX in immune system cells.